Thermal imaging and the fourth amendment:Kyllo v. U.S - Hughes, Thomas W. (American journal of criminal justice, 2001)
The Fourth Amendment protects persons from unreasonable searches and seizures. The extent to which the availability of new technology will impact this protection is an evolving area. One practice, police use of thermal imaging technology, has engendered substantial division in the courts. Recently, however, the United States Supreme Court addressed this issue in the case of Kyllo v. U.S. (2001). The Court determined that the pre-warrant use of thermal imaging machinery was a “search” under the Fourth Amendment and, thus, unconstitutional in nature. This paper traces the case development and examines the issues raised therein.